ALK‐positive compound Spitz nevus with extensive perineural and intraneural neurotropism. (8th November 2020) - Brown, Ryanne A.; Wang, Jennifer Y.; Raghavan, Shyam S.; Zhang, Jingjing; Wan, Derrick C.; Born, Donald; Koo, Matthew; Hazard, Florette K.; Novoa, Roberto A.; Rieger, Kerri E.
Abstract: Historically recognized by their characteristic histopathologic features, Spitz neoplasms are now known to be molecularly defined by mutually exclusive recurrent abnormalities that cause activation of the MAPK pathway. Spitz neoplasms with ALK rearrangements frequently demonstrate polypoid growth with a plexiform arrangement of nested, fusiform melanocytes in intersecting fascicles. Although neurotropism has been described in indolent Spitz neoplasms, this feature is not frequently mentioned in publications on histopathologic assessment of this group of melanocytic tumors. Here, we present an unusual case of a 3‐year‐old female with an ALK‐positive compound Spitz nevus with extensive perineural and intraneural neurotropism occurring on the vermilion border of the lower lip.